Measuring Success in Small Family Businesses - A Socioemotional Wealth Perspective - Bujan Ivana (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
The goal of this paper is to reveal typical non-financial success measures in small family business in Croatia. Socioemotional wealth model is used as a basis for questionnaire construction. Questionnaire items represent family typical success measures and are adaptable to different business activities. Since family business is heterogeneous it was necessary to give a definition of chosen sample – small family hotels. Given definition of small family business was used as a key to separate the family and non-family businesses in this survey. Chosen, socioemotional based, success measures were tested on a sample of small family hotels by using logistic regression. Based on the statistical results, community acknowledgments and continuation of family business are the most important non-financial success measures for Croatian example.
Keywords: D10; L25; L26; M21; 330; family firm management; family entrepreneurship; socioemotional wealth